Are followers satisfied with conscientious leaders? The moderating influence of leader role authenticity. (27th December 2018) - Harris, T. Brad; Cardador, M. Teresa; Cole, Michael S.; Mistry, Sal; Kirkman, Bradley L.
Summary: Leadership scholars have yet to identify a clear and consistent relationship between leader conscientiousness and followers' satisfaction with a leader. Drawing from socioanalytic theory and related personality research, we argue that the underlying motives of leader conscientiousness can manifest in systematically different behaviors aimed at team task accomplishment, ranging from rigid and order‐driven to relatively more adaptable approaches. Importantly, we posit that the relationship between a leader's conscientiousness and adaptability is conditioned by role authenticity (i.e., the extent to which a leader believes a role permits expressions of her or his "true self"). Hence, we articulate a conditional indirect effects model whereby leader conscientiousness and leader role authenticity jointly predict leader adaptability and, in turn, increasing levels of leader adaptability are positively associated with followers' shared satisfaction with their leader. Data from a sample of fire and rescue crews provide partial support for the model. Post hoc analyses suggest that the conditioning influence of leader role authenticity on leader conscientiousness is more informative when subfacets of conscientiousness are considered.